Six Sigma and the application perspectives of various industries: A bibliometric analysis - Mendoza-Loyo, Kevin Luis; Vázquez-Rosas, Sergio; Caballero-López, Emma Isabel; Hernández-Sánchez, Uriel Alejandro (International Journal of Advanced Engineering, Management and Science, 2020)
In recent years, quality in companies has become a priority issue which, according to the organization, is a matter of very little investment and dedication in the production lines, so a quality tool can be the solution to this problem. The present research work is to demonstrate the state of the art on Six Sigma and the perspectives in several industries through a bibliometric analysis using Bibliometrix. A database from Scopus is used, which includes a total of 857 articles in a time span from 2016 to 2020. From the results obtained, some characteristics of the articles are illustrated and analyzed (keywords, main authors, country of origin, main journals, scientific production and collaborative networks). The results obtained from the analysis show the existence of an exponential increase trend on Six sigma, being the basis for improving the quality of the processes.